2011
DOI: 10.1007/s00428-010-1011-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined small-cell carcinoma of the lung with quadripartite differentiation of epithelial, neuroendocrine, skeletal muscle, and myofibroblastic type

Abstract: The combined variant of small-cell lung carcinoma (SCLC) refers to the variable admixture of small cell and non-small cell carcinoma, whereas the association with sarcoma or sarcoma-like elements is exceedingly rare. A 76-year-old Caucasian man underwent right upper lobectomy with regional lymphadenectomy because of a symptomatic 7 cm-sized tumor mass. Formalin fixed-paraffin embedded material was used to highlight several differentiation cell lineages by means of immunohistochemistry, electron microscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Additionally, SCLCs are typically much more sensitive to chemotherapy and/or radiation therapy than are NSCLCs [20], [21]. One challenge in proper classification and treatment of lung cancer is the extreme heterogeneity caused by differing genetic, biological, and clinical properties, including response to treatment, with over 50 histological variants recognized by the WHO typing system [22], [23]. Because of this, correct classification of lung cancer cases is necessary to assure that patients receive optimum management [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SCLCs are typically much more sensitive to chemotherapy and/or radiation therapy than are NSCLCs [20], [21]. One challenge in proper classification and treatment of lung cancer is the extreme heterogeneity caused by differing genetic, biological, and clinical properties, including response to treatment, with over 50 histological variants recognized by the WHO typing system [22], [23]. Because of this, correct classification of lung cancer cases is necessary to assure that patients receive optimum management [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although our histological and immunohistochemical findings suggest that SCLC gave rise to the SLC, which in turn gave rise to the SpCC, this could not be confirmed with the molecular study. To date, there have been several molecular studies of cSCLCs . Most suggested that the SCLC and non‐SCLC components of cSCLCs had the same origin: they had identical mutations in the p53 and EGFR (exon 21) genes, as well as common LOH at 3p .…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been several molecular studies of cSCLCs . Most suggested that the SCLC and non‐SCLC components of cSCLCs had the same origin: they had identical mutations in the p53 and EGFR (exon 21) genes, as well as common LOH at 3p . In a study by Zhao et al ., approximately 75% of the mutations examined by next‐generation sequencing were shared between SCLC and non‐SCLC components .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations